Addiction vulnerability among immigrant youth: Psychosocial risk, protective processes, and intervention approaches - Özler Ervüz, Feyza; Ervüz, Cezmi; Südüpak, Şeyma (Addicta: The Turkish Journal on Addictions, 2026)
Addiction among immigrant youth is a phenomenon associated with individual experiences, family relationships, and social environment. The migration experience constitutes an important context shaping this phenomenon. Although the literature on this topic has expanded, comprehensive studies addressing addiction together with psychosocial risk factors, protective processes, and intervention approaches remain limited. This study aims to examine addiction among immigrant youth within these three dimensions. The study employs document analysis. In this context, studies indexed in Web of Science, Scopus, and Google Scholar were reviewed, and the findings were analyzed thematically. The findings indicate that three main domains shape addiction among immigrant youth. Psychosocial risk factors include trauma exposure, family disruption, and social exclusion. In contrast, protective processes such as family support, emotional regulation, cultural identity, and school connectedness mitigate these effects. Intervention approaches are primarily structured around family-based, culturally adapted, and psychosocial support-oriented models. Overall, addiction among immigrant youth emerges as a phenomenon that requires the joint consideration of psychosocial factors operating at different levels. These findings suggest that intervention approaches should be addressed within a contextual and multidimensional framework.
Keywords: immigrant youth; addiction; psychosocial risk factors; protective processes; intervention approaches; document analysis